Tracing the flows of copper and copper alloys in the Early Iron Age societies of the eastern Eurasian steppe. (April 2016) - Hsu, Yiu-Kang; Bray, Peter J.; Hommel, Peter; Pollard, A. Mark; Rawson, Jessica
Abstract: Abstract : Early Iron Age pastoralists of the Eurasian steppes relied heavily on copper for weapons and ornaments, and new analysis of metal composition enables long-distance networks to be identified. Primary circulation from source areas where copper was mined can be distinguished alongside the secondary circulation of alloy types with high proportions of tin-bronze or leaded tin-bronze. The relative presence of trace elements, depleted during recycling events, provides a proxy for the flow of metal between regions. The localised seasonal movements characteristic of these mobile steppe societies underlie some of these patterns, but the evidence also indicates more extensive transfers, including the direct movement of finished objects over considerable distances.